2016
DOI: 10.1007/s40261-016-0375-1
|View full text |Cite
|
Sign up to set email alerts
|

5-HT3 Receptor Antagonists for Propofol Injection Pain: A Meta-Analysis of Randomized Controlled Trials

Abstract: Our meta-analysis indicates that 5-HT3 receptor antagonists can effectively reduce the incidence and severity of propofol injection pain. Additionally, 5-HT3 receptor antagonists may become the alternatives to lidocaine in attenuating propofol injection pain. However, evidence is still limited for the safety of 5-HT3 receptor antagonists on propofol injection pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Micro to macro (M2M) as an advanced procedure for destabilizing the propofol microemulsions straightly before intravenous delivery of it has been developed properly. Through this novel procedure more stability could be achieved and simultaneously the injection pain would reduce potentially [45].…”
Section: Derivatives and Modification Of Propofol Agentsmentioning
confidence: 99%
“…Micro to macro (M2M) as an advanced procedure for destabilizing the propofol microemulsions straightly before intravenous delivery of it has been developed properly. Through this novel procedure more stability could be achieved and simultaneously the injection pain would reduce potentially [45].…”
Section: Derivatives and Modification Of Propofol Agentsmentioning
confidence: 99%
“…The exact mechanism of pain on injection is not known. Factors that appear to influence the incidence and the severity of pain include menstrual cycle, temperature, injection rate, infusion equipment, concentration of propofol, patient age, venous occlusion, and pretreatment medications 34 .…”
Section: New Innovations In Drug Developmentmentioning
confidence: 99%
“…3 Several interventions have been advocated to alleviate the pain associated with propofol injection, which include addition of lignocaine, ketamine, 4 acetaminophen, 5 tramadol, 6 different doses of lidocaine, 7 and different concentrations of propofol 8 and topical nitroglycerin. 9 Other studies have suggested other methods for controlling pain, including the injection of low doses of narcotics such as sufentanil and butorphanol 10,11 injection in large vessels and lignocaine injection together with tourniquet closure, 12 cold or warm propofol, 13 metoclopramide injection as a premedication, 14 magnesium, 15 beta blocker, 16 midazolam, 17 5-HT3 receptor antagonists, 18 or Alpha-2 agonists like dexmedetomidine. 19…”
Section: Introductionmentioning
confidence: 99%